Improved biomonitoring of airborne contaminants by combined use of holm oak leaves and epiphytic moss - De Nicola, F.; Spagnuolo, V.; Baldantoni, D.; Sessa, L.; Alfani, A.; Bargagli, R.; Monaci, F.; Terracciano, S.; Giordano, S. (CHEMOSPHERE, 2013)
Concentrations of 12 elements (Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn) and 16 EPA-listed PAHs were detected in Quercus ilex leaves and the epiphytic moss Leptodon smithii collected at urban, periurban and extraurban holm oak stands, in two Italian Regions (Campania and Tuscany). Levels of environmental contaminants were generally higher in leaves and moss from urban areas than periurban and extraurban ones and samples from Campania had the highest PAH content. The epiphytic moss accumulated higher concentrations of trace elements than leaves and the latter showed a higher accumulation capability for PAHs, especially for those with low molecular weight. The different bioaccumulation in leaves and moss were explained in terms of their distinctive morphological and ecophysiological characteristics. The combined approach seems a promising tool for the monitoring of a wide range of pollutants in Mediterranean urban and extraurban environments. (C) 2013 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Air pollution gradient; Bioaccumulation; Leptodon smithii; PAHs; Quercus ilex; Trace Elements